Formulation and Evaluation of Face Mask Gel Peel Off Combination of Avocado Leaf Extract (Perssea Americana Mill) and Jicama (Pachyrrhuzul Erosus L.) - Jamilatun, Makhabbah; Pratiwi, Melinda Dwi; Yulianto, Susilo (PT FORMOSA CENDEKIA GLOBAL, 2024)
Avocado leaves and jicama contain antioxidants. Topical use of antioxidants can reduce UVA radiation which can cause skin darkening. Utilization of avocado leaves and jicama is done by making a peel-off gel facial mask. This research was conducted to formulate and determine the physical quality of a gel peel-off facial mask combination of avocado and jicama leaf extracts. The quantitative experimental method was used and four formulas for varying the concentration of the active substance were prepared, with a comparison of the total extracts used, avocado and jicama leaf extracts. The combination of avocado leaf extract and jicama can be formulated as a gel peel off facial mask, with the results of physical evaluation have met the requirements.